2019
DOI: 10.1002/smll.201903025
|View full text |Cite
|
Sign up to set email alerts
|

Dielectric‐Screening Reduction‐Induced Large Transport Gap in Suspended Sub‐10 nm Graphene Nanoribbon Functional Devices

Abstract: The predicted quasiparticle energy gap of more than 1 eV in sub‐6 nm graphene nanoribbons (GNRs) is elusive, as it is strongly suppressed by the substrate dielectric screening. The number of techniques that can produce suspended high‐quality and electrically contacted GNRs is small. The helium ion beam milling technique is capable of achieving sub‐5 nm patterning; however, the functional device fabrication and the electrical characteristics are not yet reported. Here, the electrical transport measurement of su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 45 publications
0
8
0
Order By: Relevance
“…1,43 By contrast, the vertical precision of defects generated in planar 2D materials is readily below 1 nm. The bottom left part of indicates the precision of STM induced desorption 44 as well as xenon, 16 argon 17 and helium 45 ion bombardment of single layer MoS 2 (black squares) together with helium ion [18][19][20] and TEM treated 22 suspended graphene (white circles). The yellow square shows the precision of our HIM approach in single layer MoS 2 supported on graphene/SiC.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…1,43 By contrast, the vertical precision of defects generated in planar 2D materials is readily below 1 nm. The bottom left part of indicates the precision of STM induced desorption 44 as well as xenon, 16 argon 17 and helium 45 ion bombardment of single layer MoS 2 (black squares) together with helium ion [18][19][20] and TEM treated 22 suspended graphene (white circles). The yellow square shows the precision of our HIM approach in single layer MoS 2 supported on graphene/SiC.…”
mentioning
confidence: 99%
“…For suspended layers, including graphene and MoS 2 layers, the absence of backscattering from the substrate explains the enhanced lateral precision observed with helium ion and electron bombardment. [18][19][20]22,34 In principle, the best lateral precision on the atomic scale is reached for manipulation of surface atoms in STM 46 and beam induced defect generation in TEM, whereby the latter has in principle subangstrom resolution. However, due to their limited field of view and incompatibility with existing wafer processing technologies, STM and TEM are not amenable to defect creation on larger device scales, and they are of This document is the unedited Author's version of a Submitted Work that was subsequently accepted for publication in Nano Letters, ©American Chemical Society, after peer-review.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…, identical pitch), which will be paramount in multichannel FETs, can be easily fabricated by this approach. , However, GNRs obtained by electron-beam lithography are generally more than 10 nm wide, which is insufficient to induce a technologically relevant band gap ≫ k B T of 25 meV at room temperature . Even narrower GNRs have been reported via exploratory lithographic techniques such as helium ion beam lithography, meniscus mask lithography, block copolymer lithography, ,, graphene edge lithography, and scanning tunneling microscopy (STM) lithography . However, these nonconventional lithographic techniques are either unscalable or unexplored for high-volume manufacturing .…”
Section: Current State Of Graphene Nanoribbon Research and Challengesmentioning
confidence: 99%
“…This dichotomy is further evidenced by the demonstration of superior FET performance using GNRs grown heteroepitaxially in h-BN trenches that may possess mixed edge character . Research toward reducing edge roughness, similar to that demonstrated using helium ion lithography and neutral beam etching (instead of reactive-ion etching), could prove useful . Reduction of edge roughness, increased width uniformity, and improved electronic performance might also be achieved, for instance, via post-lithography edge-annealing (Figure a), , controlled gas-phase/plasma etching, , and passivation schemes such as hydrogenation. , …”
Section: Perspectivesmentioning
confidence: 99%